Meta-análisis de la resistencia a la compresión no confinada de suelos estabilizados con Xanthan - Arbulu, Cesar (2025)
Soil stabilization is aimed at improving the characteristics of soils with technical limitations through the incorporation of additional materials, thus generating soils that are optimized to support structural loads andprevent geotechnical damage. Biostabilization employs biological methods as an alternative to the use of cement, the use of which has serious environmental consequences. The extracellular bacterial polysaccharide called Xanthan gum has been studied as a soil stabilizer. However, the diversity of results in the scientific literature underlines the need for a consolidation of the observed effects on the geotechnical property of simple compressive strength. In the present study, the values of simple compression documented in indexed articles were consolidated through a meta-analysis of 27 articles. The main findings include the development of a response surface for simple compression values in different types of soils, considering varied curing times and different dosages of Xanthan gum. It is concluded that the amount of Xanthan gum applied to the soil can be classified into micro, meso and macro dosages. Also, the curing periods required to achieve strength improvements range from a few hours to several months. The effectiveness of Xanthan gum in increasing simple compressive strength is strongly influenced by soil type; it has been determined that strength can be quadrupled in clays. Finally, the main knowledge gaps related to soil stabilization by Xanthan gum have been identified.